Factors That Influence the Return to Sport After Arthroscopic Bankart Repair for Glenohumeral Instability - Rossi LA; Pasqualini I; Tanoira I; Ranalletta M (Dove Medical Press, 2022)
Luciano Andrés Rossi, Ignacio Pasqualini, Ignacio Tanoira, Maximiliano Ranalletta Hospital Italiano de Buenos Aires, Investigation Performed at the Shoulder Unit Department of Orthopedic Surgery, Buenos Aires, ArgentinaCorrespondence: Luciano Andrés Rossi, Peron 4190 (C1199ABB), Buenos Aires, Argentina, Email luciano.rossi@hospitalitaliano.org.arAbstract: Numerous studies have reported high rates of return to sports following arthroscopic Bankart repair (ABR) However, there is enormous controversy regarding the optimal management of these patients in the postoperative period. Controversy issues include rehabilitation, criteria for returning to sports, and the specific management of each athlete according to the sport they practice. Even though there are several rehabilitation protocols published in the literature, wide variability exists concerning the key elements of rehabilitation after an ABR. Regarding criteria for return to sports, there is a wide variation across the different published studies. The type of sports has been shown to affect an athlete's decision to return to sports. Nevertheless, most research is evaluated by classifications that cluster different sports into categories that may have other influences in return to sports when analyzed separately. Finally, in addition to physical readiness, the athlete's psychological state is crucial for returning to sports. However, the contribution of psychological readiness to an athlete's return to sports after shoulder instability surgery remains uncertain and unexplored.Keywords: return to sports, Bankart, anterior shoulder instability, arthroscopy